Complexаtion of scandium upon its extraction by N-(2-hydroxy-5-nonylbenzyl)-β-hydroxyethylmethylamine (NBEA-2) from chloride solutions in octanol - D. V. Bychenkov; S. A. Semenov; A. M. Reznik (Тонкие химические технологии, 2010)
Chemical aspects of scandium solvent extraction from its chloride solutions at pH 3.0-4.5 by N-(2-hydroxy-5-nonylbenzyl)-β-hydroxyethylmethylamine solutions in octanol have been studied. The extraction mechanism has been suggested. The structure of the extracted complex has been identified by 1H NMR and IR spectroscopy methods.